Symptomatic pseudoarthrosis secondary to a stress fracture of the acromion - Tagliapietra, Jacopo; Fantoni, Ilaria; Taglialavoro, Giuseppe; Angelini, Andrea; Berizzi, Antonio; Belluzzi, Elisa; Pozzuoli, Assunta; Ruggieri, Pietro (Acta Biomedica Atenei Parmensis, 2019)
Fractures of the acromion are uncommon clinical entities, and stress fractures are even more rare, with few cases reported. Due to their rarity, stress fractures are often misdiagnosed. Here, we report a case of an elderly patient with an acromion stress fracture, which was overlooked, resulting in nonunion followed by the displacement of the distal portion of the acromion. The purpose of this report was to discuss this rare fracture, highlighting the importance of an accurate evaluation of radiological imaging as well as clinical data. (www.actabiomedica.it)